Processes of social learning in the tool use of chimpanzees (Pan troglodytes) and human children (Homo sapiens) - Nagell, K; Olguin, R S; Tomasello, M (Journal of comparative psychology (1983), 1993)
Common chimpanzees (Pan troglodytes) and 2-year-old human children (Homo sapiens) were presented with a rakelike tool and a desirable but out-of-reach object. One group of subjects observed a human demonstrator use the tool in one way, and another group observed a demonstrator use the tool in another way. Children in both cases did what the model did. Chimpanzee subjects, however, behaved identically in the 2 model conditions. Both groups performed better than subjects who saw no demonstration. This pattern of results suggest that the chimpanzees were paying attention to the general functional relations in the task and to the results obtained by the demonstrator but not to the actual methods of tool use demonstrated. Human children were focused on the demonstrator's actual methods of tool use (her behavior). The different social learning processes used by the 2 species have implications for their different forms of social organization.